MICROSERVICES WITH ASP .NET CORE AND OOP DESIGN PRINCIPLES - Vamshi Krishna Jakkula; Subramanya Shashank Gollapudi Venkata; Ayush Jaiswal (Utilitas Mathematica, 2025)
Microservices are now the de facto architecture to build scalable and resilient systems and it is even more apparent in the age of distributed computing. ASP.NET Core is one of the top frameworks to build such systems because of the modularity, cross-platform ability, and capability to work in cloud-native settings. At the same time, object-oriented principles (OOP), particularly, object incorporation, object modularity, and polymorphism, remain strong practices of the software design, but there is a research gap to correlate them to microservices systems. This paper investigates the implementation of OOP concepts in ASP.NET Core-based microservices and examines how this approach can be used in the area of system design, ease of maintenance, and performance amelioration. Thematic synthesis of peer-reviewed literature, case studies, and technicaldocumentation were used as a qualitative research method. Architecture patterns that are based on a code, including Dependency Injection, Domain-Driven Design, and asynchronous messaging, have been examined. The results indicate that the great benefit of OOP and principles, implemented through SOLID-conformant service, the interface-based approach to contracts, and through the Repository or Factory design patterns can be achieved through the scalability of the application, decoupling, and long-term support. Experimental deployments with Docker and Kubernetes demonstrated up to 35% performance improvement and improved fault tolerance. Also, the flexibility of ASP.NET Core makes it possible to merge it with other more modern paradigms like declarative logic, IoT-based workflows, and an event-driven architecture. These findings affirm that OOP is not just comprehensible with microservices in ASP.NET Core but is anyhow structurally fundamental to their effectiveness since it can offer a perfect theoretical framework or even practice useful benefits in developing long-lasting enterprise-level distributed frameworks.